ANALISIS SISTEM PENGENDALIAN INTERN TERHADAP PERSEDIAAN PT. TIRTA RAYA ABADI MEDAN - Siti Julia Anggrayati; Syaharman Syaharman (UNIVERSITAS DHARMAWANGSA, 2022)
Inrent assets and is the center of activity and the main source of the company. Inventory is also an asset that is sensitive to damage, theft and decline in market value, so that inventory control is very necessary because negligence in managing inventory can result in losses for the company. In carrying out inventory management, it is necessary to have a good inventory management system and management. It is necessary to have a correct understanding of the goods control system so that the effectiveness and efficiency of the company can be maintained. The types and sources of data used in the preparation of this research are primary data and secondary data.The data collection methods used in this study were interviews, observations, literature review, and documentation studies. The data analysis technique used in this research is a qualitative technique. The results showed that the inventory control system at PT. Tirta Raya Abadi Medan has not run effectively. This is due to the fact that inventory management is still done manually, with limited staff in charge of stock control (one person). This causes the stock control staff to be vulnerable to not being aware of errors due to their routine. Not all warehouse employees are able to carry out internal control of the physical goods because there ventory is a very important asset in the company because inventory is one of the largest parts of curare too few warehouse staff and it is done manually so it takes a long time to check goods